The importance of consumer awareness towards fire protection in their household / Sarah Shafiqah Ahmad Zulkifli - Ahmad Zulkifli, Sarah Shafiqah (Universiti Teknologi MARA, Johor, 2017)
Fire Fighter Industry Sdn Bhd was established in 1974 and now is the Malaysia's market leaders in the industry of fire prevention and protection. They are ISO-certified in manufacturing, installation and maintenance of a full range of fire protection systems and their ancillary equipment. Fire Fighter@ has built its reputation by earning the consumers' trust and delivering exceptional quality with value prices. The issue that the researcher had decided to do this research is because consumers nowadays are not aware of the important of the fire safety in their household and their life. Therefore, the loss of life and property caused by fire are most commonly occurring because of ignorance about the nature of fire and its behaviour. Thus, the objective of this research is to identify the main factors that influence between safety, knowledge and prevention in consumer awareness towards fire protection in their home. Moreover, the researcher decided to use a simple random sampling where it is a subset of a statically population in which is each member of the subset has an equal probability of being chosen. After that, simple random sample is meant to be unbiased representation of a group. Furthermore, the data that had been collected by the researcher is by distributed 50 questionnaires to the respondents in Subang Jaya and Petaling Jaya. Then, all the data that had been collected were analysed through the SPSS software. Lastly in this research, shows that both of the variables have been accepted in the hypothesis in this research.